Visual Image of Architectural Elements in Kampung Al Munawar Palembang - Agus S Sadana; Ashri Prawesthi D (Department of Architecture Universitas Muhammadiyah Jakarta, 2020)
Kampung Al Munawar is a tourist village located in the Palembang city. This place is interesting because located on the banks of the Musi river and has a nice layout form. There is an interesting term in naming the place in this village, there are land and sea area. Land area is part of the village tends towards the land, sea area is part of the village located on the banks of the Musi big river. Some unique elements in this village are found by visitors' sight and remembered in their minds, in a form known as a mental map or mental image. This research combines descriptive, graphical and quantitative analysis methods to describe mental map or mental image recorded in observer’s mind. The results of the mental image show the unique gradation of places and objects remembered by visitors. The result shows the land entrance area and river pier area are both remembered only by 86% of observers. Row of houses leading to the sea remembered by 93% of observers. Row of houses and open space in the center of the village remembered by all of observers. This means that the core area attracts more visitors than its entrance and river’s banks area. Though Kampung Al Munawar can be a more interesting place if it is reached from the riverside. Therefore need to develop more activities in the riverbank area and increase the pier aesthetics, to attract visitors through the river and make the seaside more meaningful.